Spatial distribution of nanodiamond and its effect on mechanical behaviour of epoxy based composite using 2D modulus mapping. (August 2019) - Bisht, Ankita; Kumar, R. Manoj; Dasgupta, Kinshuk; Lahiri, Debrupa
Highlights: 2D modulus-mapping was used to understand the distribution of nanophase reinforcement in polymer matrix and their behaviour during loading. Numerical analysis was used for predicting the elastic property of ND-epoxy composite based on the findings from modulus-mapping. The values of elastic modulus obtained from numerical analysis were in good agreement with that obtained from instrumented indentation. Abstract: The present study has taken an initiative to understand the distribution of nanophase reinforcement in polymer matrix and their behaviour during loading, using 2D modulus mapping. The composite system, being studied here, is a nanodiamond reinforced epoxy resin matrix. Modulus Mapping gives an idea of distribution of nanodiamond in matrix, in terms of spatial distribution of micron level higher modulus regions in epoxy matrix. The modulus mapping studies, carried out on composites with and without application of uniaxial tensile stresses, reveals the active role being played by nanodiamond in modulating the mechanical behaviour of the epoxy matrix and the evolution of distribution of the former with application of stress. Hardness and elastic modulus of epoxy is improved by ∼470% and ∼94% with 1 wt% nanodiamond. The stiffening effect of nanodiamond dispersed in epoxy matrix, evaluated through experiment is also in concurrence with results simulated using finite element method (FEM) of the representative volume element (RVE). Tensile strength and fracture toughness also showed an improvement of ∼56% and ∼85%, respectively, with 0.3 wt% ND. Interestingly, % strain (at break) also increased by ∼66%. TEM showed good dispersion and strong interaction of NDs with epoxy matrix. SEM analysis validates crack pinning and crack deflection as dominant toughening mechanism, while, efficient load sharing between ND and epoxy is found as main strengthening mechanism. As a whole, this study develops 2D modulus mapping technique as a generalized tool for evaluating the quality of dispersion of the nanoscale reinforcement phases and their role in mechanical behaviour of the macro-scale composite structures. Graphical abstract: Image, graphical abstract